Evaluation of Oral Antidiabetic Dosing and Drug Interactions in Type 2 Diabetic Patients - Nova Hasani Furdiyanti; Fania Putri Luhurningtyas; Ratna Sari; Yulianti Yulianti (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Indonesia is listed as the country with the highest type 2 diabetes mellitus patients number 4 in the world. Accuracy of treatment is necessary in the success of therapy for type 2 diabetes mellitus patients. Inaccurate dosage or drug interaction events can lead to treatment failure or even cause adverse effects in patients. Patients with type 2 diabetes mellitus usually have comorbidities that tend to get therapy with many drugs, thus increasing the risk of drug interactions. Drug interactions with oral antidiabetes are known to exist that can be life-threatening. The aim of this research is to know the accuracy of dose of oral antidiabetika drug and drug interaction event in type 2 diabetes mellitus patient. This research is a descriptive retrospective observational study. Data collection is done retrospectively, and sampling method is purposive sampling. Research subjects were all inpatients of type 2 diabetes mellitus 26 - 65 years old, who received oral antidiabetes therapy period 2016 at RS Sultan Agung Semarang, and meet the criteria of inclusion and exclusion. The data analyzed the incidence of drug interaction and dosage accuracy (based on dose parameter and frequency of administration). The results of the study in 86 subjects showed that the most widely used single therapy was metformin (50,98%) while the most used combination therapy was metformin and glimepiride (57,14%) .The incidence of drug interaction was 5%, between glimepiride and aspirin with a pharmacokinetic mechanism occurring in 4 patients. The percentage of inaccurate doses of oral antidiabetic drugs was 3.5%, which occurred in patients taking metformin and acarbose.